ISIS and Crisis of Statehood in the Middle East - F. S. Zamuruev (Vestnik MGIMO-Universiteta)
Abu-Rumman Mohammad, Abu Hanieh Hassan. The 'Islamic State' Organization: the Sunni crisis and the struggle of global jihadism. Amman: Friedrich-Ebert-Stiftung, 2015. - 272 p. = 4 MB, PDF-File. - Electronic ed.: Amman : FES, 2015. - Arabic script. ISBN 978-9957-484-50-7. http://library.fes.de/pdf-files/bueros/amman/11262.pdf (in Arabic), http://library.fes.de/pdf-files/bueros/amman/11458.pdf.